Enhancing Employee Performance Through Work Culture and Discipline: A Case Study of PT. Pilarco Karawang - Kemal, Ramdhia; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine the partial and simultaneous influence of work culture and work discipline on employee performance at PT Pilarco Karawang. The method used is descriptive verification. This research was conducted on employees of PT Pilarco Karawang, with a sample size of 80 workers. The Simple Random Sampling method with saturated samples was used as the sampling methodology. Multiple linear regression analysis, including the F test and T test with a significance threshold of 5%, was employed to analyze the data. The findings indicate a partial contribution of work culture to employee performance at PT Pilarco Karawang, with a t-value of 26.387 > 1.991 (tcount > ttable). Employee performance at PT Pilarco Karawang is also partially influenced by work discipline, as shown by the t-value (45.737 > 1.991, or tcount > ttable). Work culture and work discipline collectively account for 96.5% of the performance of PT Pilarco Karawang employees, while the remaining 3.5% is influenced by other factors not examined in this study.